1994
DOI: 10.1128/aac.38.4.830
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of antibiotics during human necrotizing pancreatitis

Abstract: The aim of the study was to verify whether antibiotics excreted by the normal pancreas are also excreted in human necrotizing pancreatitis, reaching the tissue sites of the infection. Twelve patients suffering from acute necrotizing pancreatitis were treated with imipenem-cilastatin (0.5 g), mezlocillin (2 g), gentamicin (0.08 g), amikacin (0.5 g), pefloxacin (0.4 g), and metronidazole (0.5 g). Serum and necrotic samples were collected simultaneously at diferent time intervals after parenteral drug administrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
73
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(77 citation statements)
references
References 36 publications
2
73
0
Order By: Relevance
“…However, the advantage was limited to patients with severe pancreatitis who received broad-spectrum antibiotics that achieved therapeutic pancreatic tissue levels. Büchler [75][76][77] and others have identified imipenem as the antibiotic agent of first choice because it reached higher pancreatic tissue levels and provided higher bactericidal activity against most of the bacteria present in pancreatic infection compared to other types of antibiotics. An alternative antibiotic regimen is either ciprofloxacin or ofloxacin in combination with metronidazole, although a previous trial has not shown any benefit with this regimen [78].…”
Section: Management Of Acute Pancreatitis In Phase IImentioning
confidence: 99%
“…However, the advantage was limited to patients with severe pancreatitis who received broad-spectrum antibiotics that achieved therapeutic pancreatic tissue levels. Büchler [75][76][77] and others have identified imipenem as the antibiotic agent of first choice because it reached higher pancreatic tissue levels and provided higher bactericidal activity against most of the bacteria present in pancreatic infection compared to other types of antibiotics. An alternative antibiotic regimen is either ciprofloxacin or ofloxacin in combination with metronidazole, although a previous trial has not shown any benefit with this regimen [78].…”
Section: Management Of Acute Pancreatitis In Phase IImentioning
confidence: 99%
“…Few broad-spectrum antibiotics present appropriate characteristics for the treatment of pancreatic tissue infections (2,6,20,22,25). ␤-Lactam drugs exhibit time-dependent bactericidal activity, extravascular distribution, and tissue extracellular fluid concentration: the therapeutic goal is to optimize the duration of antimicrobial exposure (10,18).…”
mentioning
confidence: 99%
“…This is a critical point for infections caused by gram-negative bacilli (9, 23) and for particular infection sites, such as the pancreas (2-4, 6). ␤-Lactam agents are useful for treatment of infected acute necrotizing pancreatitis (1,2,6,8,11,25), a disease associated with a high mortality rate (7,24).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Drug concentrations were deduced by log-linear regression from published data following infusions of 400 mg moxifloxacin (22) and 1,000 mg each of imipenem (3,18) and ertapenem (24). The following maximal total drug concentrations (C max ), time to C max (T max ), and elimination half-life (t 1/2 ) in human pancreatic tissue were deduced from these published data: for moxifloxacin, C max ϭ 4.6 mg/liter, T max ϭ 5 h, and t 1/2 ϭ 8; for imipenem, C max ϭ 16 mg/liter, T max ϭ 0.25 h, and t 1/2 ϭ 1.3 h; for ertapenem, C max ϭ 1.3 mg/liter, T max ϭ 0.5 h, and t 1/2 ϭ 4 h. For calculation of free drug concentrations, the following was considered.…”
mentioning
confidence: 99%